(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article describes a set of exercises in forming of the speech competence, gives the system of exercises. When implemented sequentially in a class, the exercises will help develop logical culture on the lessons of foreign language.